Haematological Response of Crossbred Lambs Fed Complete Diets Supplemented with Exogenous Fibrolytic Enzymes Cocktail or Artemisia absinthium L. Herb Alone and in Combination - Beigh, Yasir Afzal; Ganai, Abdul Majeed; Sheikh, Gowhar Gull; Mir, Masood Saleem; Amin, Umar (Indian Journal of Animal Nutrition, 2018)
The present study was planned to assess the effect of supplementation of exogenous fibrolytic enzyme (EFE) cocktail and Artemisia absinthium L. (Afsanteen) herb alone and in combination as feed additives in oats straw based complete diet on complete haemogram in crossbred lambs. Twenty crossbred lambs randomly divided into four groups of five animals in each were fed individually for a period of 90 days. Animals in all the groups were offered complete feeds containing (% parts): (oats straw- 40, mixed grass hay- 20 and concentrate mixture- 40). The complete feeds were supplemented either alone with EFE cocktail (T1) @ 6 g/kg DM or Afsanteen herb (T2) @ 4.5% of DM and combination of the two feed additives (T3) whereas the complete feed without any supplementation served as control (T0). There were non-significant effects of feed additive supplementation on total blood cell counts, RBC and platelet indices except haematocrit, however, significant differences were recorded for DLC among the treatment groups. It could be concluded that supplementation of EFE cocktail and A. absinthium L. herb alone or in combination to complete feed did not have any adverse effect on haemogram.